Heat transfer enhancement of vertical dimpled fin array in natural convection. (March 2017) - Chang, Shyy-Woei; Wu, Horng-Wen; Guo, Da-Yu.; Shi, Jun-jie; Chen, Tang-Hong
Highlights: We study steady-state three-dimensional natural convective heat transfer for vertical fin arrays with/without dimples. We numerically solve the Navier–Stokes and energy equations to acquire velocity field and temperature field. As Rayleigh number increases, the mean Nu over each fin surface increases, especially for the dimpled fin arrays. The respective worst and best heat transfer performances are for the smooth thirteen-fin and dimpled nine-fin arrays. Relative to the smooth thirteen-fin array, the maximum increase of mean Nu is 68% for the dimpled nine-fin array. Abstract: This numerical study examines the steady-state three-dimensional natural convective flow and heat transfer for a set of vertical fin arrays with/without dimples. The finite volume method is adopted to solve the Navier–Stokes and energy equations using semi-implicit method for pressure-linked equation (SIMPLE) with the converged solutions from the iterative steps to acquire the velocity field, temperature field, and Nusselt number (Nu). The free convective flow and heat transfer for different vertical fin arrays are analyzed at Rayleigh numbers (Ra) of 10 8, 7.75 × 10 7, 5.5 × 10 7, and 3.25 × 10 7 with the fixed Prandtl number of 0.71. For each Ra tested, four vertical fin arrays, namely smooth thirteen-fin array, smooth nine-fin array, dimpled nine-fin array, and dimpled seven-fin array, with the same fin base area and fin-array volume are individually analyzed. The results indicated the respective worst and best heat transfer performances for the smooth thirteen-fin and dimpled nine-fin arrays. As Ra increases, the mean Nu over each fin surface increases, especially for the dimpled fin arrays. Relative to the smooth thirteen-fin array, the maximum increase of mean Nu is 68% for the dimpled nine-fin array.